PENGARUH PEMBERIAN AKAR PASAK BUMI (Eurycoma longifolia Jack.) TERHADAP KERUSAKAN ORGAN HATI MENCIT BUNTING (The Effect of Eurycoma longifolia Jack. Roots on Liver Damage of Pregnant Mice) - Ruqiah Ganda Putri Panjaitan; Masriani M; Zulfan Z (Jurnal Kedokteran Hewan, 2016)
This study aims to find out the eeffect of Eurycoma longifolia Jack. roots on the liver damage of pregnant mice. This research used Balb/cstrain mice, 2-3 month, with the weight ranging of 27-33 gram. Samples were divided into three treatment groups consisted of three mice. GroupI (KI) was negative control (placebo), only treated with 0.06 ml/20 g bw of distilled water, group II (KII) was administered with roots ofEurycoma longifolia Jack extract at dose of 14 mg/20 g bw, and group III (KIII, positive control) was administered with Schizandrae at the dose0.06 mg/20 g bw. Treatment were done for 7 consecutive days in pregnancy period. On day 8th, blood samples were collected to examine the levelof alanine transaminase (AST) and aspartate transaminase (ALT) enzymes in serum and liver organ were collected to observe thehistopathological changes. The average of ALT and AST enzymes level on K1, K2, and K3 were 18.34+0.28, 19.68+0.15, and 19.20+0.08 U/l; and21.79+0.26, 23.42+0.41, and 22.23+0.52 U/l. The histopathological examination results showed that the administration of E. longifolia Jackroots extract and Schizandrae reveal the karyomegali and fatty change of hepatocytes. It is concluded that the administration of E. longifoliaJack roots extract at the dose of 14 mg/20 g bw could decrease the liver function of pregnant mice. Key words: Eurycoma longfolia Jack. root, pregnancy period, liver histopathological studies